Parental stress contexts in a neonatal intensive care unit (Revista Contexto & Saúde, 2025)
This study aimed to (re)discover the stressful situations experienced by parents in the context of a Neonatal Intensive Care Unit. This is a mixed method study conducted in two Neonatal Intensive Care Units. Thirteen fathers and/or mothers of newborns participated in the interview, and quantitative data were collected using the Parental Stress Scale: Neonatal Intensive Care Unit. Bardin was used for thematic analysis. The data resulted in four thematic categories and a “talking table” that integrates the data from the quantitative and qualitative approaches. Stress is present in both methodological facets of analysis, with emphasis on the parental role domain, with the highest mean score. The findings reinforce the need to promote unique care for newborns, taking the family into consideration. In addition to efficient communication, promoting and strengthening parental co-responsibility for care, and respecting family principles are essential for the recovery and rehabilitation of newborns.
Keywords: Neonatal Intensive Care Units; Newborn; Psychological Stress; Neonatal Nursing